Dampak Program Edukasi Kedisiplinan dan Keterlibatan dalam Persekutuan Ibadah Jemaat GKSI Nanga Lungu - Hepni Putri S. (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2026)
This study aims to analyze the impact of the discipline education program on the involvement of the congregation in worship fellowship at GKSI Nanga Lungu, Kayan Hilir District, Sintang Regency, West Kalimantan. The approach used is qualitative with the method of library research and direct observation of congregation activities. The results of the study show that discipline education programs make a significant contribution to increasing congregational attendance in worship, active participation in prayer, singing, and service, as well as the formation of discipline character in daily life. In addition, this program helps strengthen social interaction between congregations, build closer spiritual bonds, and encourage involvement in various church activities. The main challenges faced include the busyness of the congregation and the distance of residence from the church, but can be overcome through adaptive strategies such as pastoral mentoring, flexible scheduling, and periodic evaluations of program effectiveness. These findings show that discipline education is an effective and relevant strategy in improving the quality of worship fellowship and the spiritual life of the congregation. This study recommends strengthening similar programs in other church settings as a sustainable and contextual spiritual development effort.